Model Pair Check Untuk Meningkatkan Hasil Belajar Matematika Materi Pecahan Pada Siswa Kelas V Sekolah Dasar - Wiratsiwi, Wendri (Universitas PGRI Adi Buana Surabaya, 2019)
This study aims to improve mathematics learning outcomes in fractional material in fifth gradeelementary school students. The research method used is a class action research method. The subjectsin this study were fifth grade students of Temaji I Elementary School, Jenu District, Tuban with 32students including 14 men and 18 women. Data collection techniques through observation techniqueswith observation of teacher activities and student activities and test techniques. The results showed anincrease from pre-cycle, which was previously only 10 students (31.25%) who reached the minimumcompleteness criteria increased to 14 students (43.75%) who completed learning, in the second cycleincreased to 19 students (59.4% ) and in cycle III also increased to 27 students (84.3%) who reachedthe minimum completeness criteria.